The Effect of Probiotic Lactobacillus paracasei on The Performance of Guppy Fish (Poecilia reticulata var. Mosaic) (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Guppy fish (Poecilia reticulata var. Mosaic) is a type of ornamental fish that has many enthusiasts. Guppy fish culture still has low growth and viability in guppy fish culture. The previous solution was to apply antibiotics, but as time goes by antibiotics cause bacterial resistance. Another solution is the application of probiotics to feed. L.paracasei is one of the lactic acid probiotic bacteria and has never been applied to guppies. This study aimed to analyze the effect of the probiotic on performance (growth and viability, gill and gut histology, and LAB (Lactic Acid Bacteria L.paracasei) total) in guppies. 180 fish were randomly assigned into four triplicates groups and there were four treatment groups: 0 (Control), 5, 10, and 15 mL. kg-1 feed. As the result of this research, the highest body weight and length growth performance is found in the P3 group. Meanwhile, there were no significant differences between the groups of guppies viability. Gill and intestinal histology showed that control group was the best group. The conclusion of this study is that 15 mL. kg-1 is considered the most effective for improving the performance of guppy fish. The addition of L.paracasei can be used as feed supplements to improve performance of guppy fish.